2019
DOI: 10.1039/c9ra01565e
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the treatment of acid mine drainage by modified corncob fixed SRB sludge particles

Abstract: A cost-effective system for acid mine drainage removal was developed with the key role of alkaline H2O2 modified corncob and sulfate reducing bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
6
0
4
Order By: Relevance
“…According to the enrichment and culture method of SRB, the seed mud was inoculated into the sterilized Starkey medium for anaerobic culture [25]. When H 2 S and black precipitate appear, SRB is cultured [26]. Then the SRB with strong activity was enriched.…”
Section: Of 21mentioning
confidence: 99%
“…According to the enrichment and culture method of SRB, the seed mud was inoculated into the sterilized Starkey medium for anaerobic culture [25]. When H 2 S and black precipitate appear, SRB is cultured [26]. Then the SRB with strong activity was enriched.…”
Section: Of 21mentioning
confidence: 99%
“…However, the growth of these bacteria requires simple carbon and nutrients that can be obtained from compost that is rich with organic matter. The compost becomes the carbon sources for triggering sulfate-reducing bacteria to reduce sulfate producing sulfide and bicarbonate that affects the rise in pH (Dong et al, 2019). When only using sediment in the treatment, the sulfatereducing bacteria do not get the energy of the oxidation of organic compounds as an electron donor to generate hydrogen sulfide under anaerobic conditions (Hu et al, 2018).…”
Section: Sulfate Concentrationmentioning
confidence: 99%
“…The results of this study were more successful in reducing sulfate of acid mine water using the estuary sediment as a source of sulfate-reducing bacteria inoculums with the addition of compost as source of nutrients, when compared to previous studies. Dong et al (2019) recently reported that the removal percentages of sulfate in a column were 52.94%, and the effluent pH value was 6.56 with treatment of acid mine water by modified corncob fixed SRB sludge particles in the column test models. Yim et al (2015) reported that passive treatment systems utilizing mushroom compost indicated a sulfate treatment efficiency of 63% within 120 days with a neutral pH value.…”
Section: Number Of Sulfate-reducing Bacteriamentioning
confidence: 99%
“…The study found that heavy metals in acid mine water can be removed by adsorption, ion exchange, reverse osmosis and other methods, but there are some disadvantages such as saturation of adsorption, susceptible to external factors, and high maintenance costs [6,7]. In recent years, microbial methods represented by sulfate-reducing bacteria (SRB) have been considered as a promising alternative to traditional methods due to their high treatment efficiency, low operating cost and strong reproducibility [8,9]. However, SRB growth is inhibited by low pH and high concentration of metal ions [10], and continuous carbon source addition and other issues have limited the large-scale application of microbial method.…”
Section: Introductionmentioning
confidence: 99%